Legal personality of the individual in international law: from its non-recognition to absolute recognition (International relations and international law Journal, 2017)
In this article it is analysed that rights and liberties of individuals determined in international legal documents first of all, regarded demonstration of will of state, the majority of international rules on human rights are abstract and for implementation of such norms rises the need of the establishment of intrastate acts. The disparities in understanding the concept of international law subject explain the lack of international legal instruments that could ascertain the exact legal positions of natural persons in question. By a thorough analysis of legal sources, the authors aimed at identifying both general legal parameters of legal personality representation in international law and its individual forms in particular, such as the rights of migrants, refugees, victims of armed conflicts, and investors as economic bloc representatives. The research demonstrates that as opposed to the positions maintained in foreign scientific literature, which tend to treat individuals as subjects of international law, the dominant point of view in the Russian doctrine of international law is the one suggesting that these persons are not subjects of international public law. In the submitted article, the authors entered upon formation of context perception of legal personality and believe that further research might be focused on assessing the degree of compliance of national legislations in coalitions.
Keywords: personality of the individual; human rights; international criminal court; responsibility